Evaluasi Struktur Kolom Kuat Balok Lemah Dengan Sistem Rangka Pemikul Momen Khusus pada Gedung Rumah Sakit Empat Lantai - Akbar Dwinanda Nugraha; Eko Walujodjati (Institut Teknologi Garut, 2026)
Indonesia is geologically located on the Ring of Fire, which means there are many active volcanoes along the Pacific plate. This is the cause of geological disasters, including earthquakes that often occur in Indonesia. According to SNI 1726:2019, there is an earthquake-resistant building concept, namely the Special Moment Bearing Frame System (SRPMK). Considering the frequent earthquakes, especially in Bandung Regency, it is very important to apply the Strong Column Weak Beam (SCWB) system to the Salman Hospital HCU (High Care Unit) building. This study aims to determine the application of the concept (SCWB) to the HCU building of Salman Hospital in an effort to anticipate damage in the event of an earthquake. The SCWB planning concept is a structural design innovation that makes the structural system flexible and allows deformation during an earthquake. This analysis starts from modeling, loading, and spectral response analysis. The calculation is carried out based on data obtained from field data with the data obtained is technical specification data and working drawings of the HCU Building of Salman Hospital. The results of the analysis show that the HCU building of RS Salman Hospital with beam dimensions of 300 x 500 and column dimensions of 450 x 450 does not meet the SCWB (Mnc â‰¥ 1.2 * (Mn- + Mn+) in accordance with SNI 2847: 2019, with a value of Mnc 110.313 kN.m and Mnb 179.200 kN.m and a redesign is required to meet the SCWB.